Model Penataan Pemakaman Sebagai Ruang Terbuka Hijau di Kota Makasar - Nurul Fahmiah; Hazairin Zubair; Andang Suryana Soma (Universitas Hasanuddin, 2021)
RTH in urban areas has undergone many changes into built-up land so that it has changed its function into settlements, hotels, restaurants and others due to the very high growth of urban activities in Makassar City. Cemeteries have the main function as a place of public service for the burial of bodies. Cemeteries can also function as green open spaces to add to the beauty of the city and can function as water catchment areas, protectors, ecosystem supporters, and unifying urban spaces. The research aims to determine the design of the appropriate burial area model that functions as green open space and determine the potential of green open space that can be maximized from the Makassar City cemetery area. Research using survey techniques and descriptive analysis of 7 TPUs in Makassar City, was carried out from July to August 2021. The results show that dense cemeteries with high land cover have reduced the function of TPU as City Green Open Space. The design of the TPU in the context of optimizing the green open space increases the capacity of the tomb and improves environmental functions and religious norms, through the addition of facilities and diversity of vegetation.